Efektifitas Model Pembelajaran Mini Basket terhadap Peningkatan Kemampuan Motorik Kasar Anak Usia 6-8 Tahun - Rohmana, Via Diah; Shandy, Dwi Kurnia; Permana, Dwinda Abi; Kodriyah, Nurma Kusnun; A’yun, Sely Qurrotul (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research analyzes the effectiveness of the mini-basketball model in improving the gross motor skills of children aged 6–8 years. Using a quasi-experimental quantitative method, participants from the 1st grade of SDN Burengan 1 were divided into an experimental group (mini-basketball) and a control group (conventional method). The testing utilized the TGMD-2 instrument, covering pretest, 14 days of treatment, and posttest. The initial results demonstrated homogeneity. Following the treatment, the posttest score of the experimental group increased significantly to 55.10 (gain +13.20), which was substantially higher than the control group (46.80, gain +4.75). Statistical tests confirmed a highly significant increase ($p < 0.001$) in the mini-basketball group.In conclusion, the mini-basketball learning model is proven to be highly effective and substantially superior compared to the conventional method in improving children's gross motor skills, as it is supported by the nature of the activity, which is enjoyable and optimal for motor practice.